Odpowiedzi

Najlepsza Odpowiedź!
2010-01-14T20:59:59+01:00
A) Ba → BaO → Ba(OH)₂
|
Ba(OH)₂
b) N₂ → N₂O₃ → N₂O₅ → HNO₃
|
HNO₃

2Ba + O₂ --> 2BaO
BaO + H₂O --> Ba(OH)₂
Ba + 2H₂O --> Ba(OH)₂ + H₂

2N₂ + 3O₂ --> 2N₂O₃
N₂O₃ + O₂ --> N₂O₅
N₂O₅ + H₂O --> 2HNO₃
N₂ + 6H₂O --> 2HNO₃ + 5H₂
1 5 1
2010-01-14T21:04:19+01:00
A) Ba → BaO → Ba(OH)₂
|
Ba(OH)₂

1)2 Ba+O₂---> 2BaO

2)BaO + H₂O---> Ba(OH)₂

3) Ba + 2 H₂O ---> Ba(OH)₂ + H₂

b) N₂ → N₂O₃ → N₂O₅ → HNO₃
|
HNO₃

1) 2N₂ + 3O₂ -----> 2N₂O₃

2)N₂O₃+ O₂ --->N₂O₅

3) N₂O₅ + H₂O --->2HNO₃
1 5 1